When donors get cold feet: the community conservation concession in Setulang (Kalimantan, Indonesia) that never happened - Wunder, Sven; Campbell, Bruce M.; Frost, P.; Sayer, Jeffrey A.; Iwan, R.; Wollenberg, Eva Karoline (2008)
There is consensus that payments for biodiversity services are a promising conservation tool, yet the implementation of applied schemes has been lagging behind. This paper explores some reasons why potential biodiversity buyers may hesitate. It describes the case of an unsuccessful attempt to establish a community conservation concession in the village of Setulang (East Kalimantan, Indonesia) to safeguard a biologically valuable area from predatory logging. Potential biodiversity donors did not engage in this payments-for-environmental-services scheme mainly because of their limited time horizon and uneasiness about the conditionality principle. Other complicating factors included overlapping land claims, and the diagnosis of the externality at hand. We conclude that new investment modalities and attitudes are needed if potential biodiversity buyers are to exploit the advantages of this innovative tool. We also provide some tangible recommendations on factors to consider when designing a compensation scheme for conservation at the community level.